Appraising strategic adaptive management as a process of organizational learning. (1st January 2022) - Roux, Dirk J.; Novellie, Peter; Smit, Izak P.J.; de Kraker, Joop; Culloch-Jones, Samantha Mc; Dziba, Luthando E.; Freitag, Stefanie; Pienaar, Danie J.
Abstract: Adaptive management is a systematic approach for linking learning with implementation to facilitate ongoing improvement in natural resource management. The idea of learning from experience and adapting subsequent policies, strategies and actions, is intuitively appealing. However, application of adaptive management has been hindered by several obstacles, including a paucity of documented lessons from existing adaptive management practices and inadequate attention to the complex social aspects of learning. Here we address these two impediments through (i) a case study of an established version of adaptive management and its application in the context of protected area management plans, and (ii) its critical comparison and conceptual integration with the seminal theory of organizational knowledge creation (TOKC), which emphasizes the social aspects of learning. As case study, we focus on Strategic Adaptive Management (SAM), which has been iteratively developed and implemented by South African National Parks for more than 20 years. We used TOKC as a conceptual sounding board to reflect on and appraise the learning that takes place through SAM. A comparison of the main steps of the SAM cycle with corresponding stages outlined by TOKC revealed remarkable complementarity between these two approaches, but also important differences. The conceptual comparison deepened our understanding of SAM's learning performance as well as potential, revealing strengths, weaknesses and opportunities for improvement. Key insights include that valuable and different forms of learning takes place during each step of the SAM cycle. This learning can be enhanced through careful attention to approaches for creating, sharing and making explicit the tacit knowledge of individuals. Furthermore, dialogue and co-learning with stakeholders should be maintained beyond the visioning and objectives setting step of SAM. Based on insights gained, we developed a new and complementary conceptualization of SAM, as a spiraling process of organizational learning enabled by the interplay between tacit and explicit forms of knowledge, which in turn is mediated by different types of social interactions, media and engagement with practice. We believe that this conceptualization can help to better acknowledge and enable learning as one of the most fundamental purposes and outcomes of SAM, and adaptive management more generally. Highlights: Multiple forms of learning take place throughout the adaptive management cycle. Attention to creation, sharing and conversion of tacit knowledge enhance learning. Stakeholder engagement can enrich learning during each step of adaptive management. Reframing adaptive management can help to catalyze learning as a central outcome.